2007
DOI: 10.1074/jbc.m703259200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Skeletal Muscle ClC-1 Chloride Channels by Low Intracellular pH and ATP

Abstract: Skeletal muscle acidosis during exercise has long been thought to be a cause of fatigue, but recent studies have shown that acidosis maintains muscle excitability and opposes fatigue by decreasing the sarcolemmal chloride conductance. ClC-1 is the primary sarcolemmal chloride channel and has a clear role in controlling muscle excitability, but recombinant ClC-1 has been reported to be activated by acidosis. Following our recent finding that intracellular ATP inhibits ClC-1, we investigated here the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 47 publications
10
83
4
Order By: Relevance
“…First, these findings validate adequate space clamp uniformity even in naive fibers because ClC-1 channel gating was unaffected by loss of a significant fraction of cell capacitance originating from the T-tubule compartment. Second, previous studies demonstrated that ClC-1 gating is strongly influenced by chloride concentration (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001), pH (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001;Bennetts et al, 2007), nitric oxide (Lin et al, 2008), and with some controversy, the binding of adenosine derivatives (Bennetts et al, 2005Tseng et al, 2007;Zhang et al, 2008;Zifarelli and Pusch, 2008). Although we did not directly test if these factors modulate native ClC-1 channel activity in FDB fibers, our findings suggest that detubulation by formamide addition and withdrawal does not markedly perturb basal modulatory influences of these factors on ClC-1 gating.…”
Section: Discussioncontrasting
confidence: 56%
“…First, these findings validate adequate space clamp uniformity even in naive fibers because ClC-1 channel gating was unaffected by loss of a significant fraction of cell capacitance originating from the T-tubule compartment. Second, previous studies demonstrated that ClC-1 gating is strongly influenced by chloride concentration (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001), pH (Rychkov et al, 1996(Rychkov et al, , 1997Accardi and Pusch, 2000;Chen and Chen, 2001;Bennetts et al, 2007), nitric oxide (Lin et al, 2008), and with some controversy, the binding of adenosine derivatives (Bennetts et al, 2005Tseng et al, 2007;Zhang et al, 2008;Zifarelli and Pusch, 2008). Although we did not directly test if these factors modulate native ClC-1 channel activity in FDB fibers, our findings suggest that detubulation by formamide addition and withdrawal does not markedly perturb basal modulatory influences of these factors on ClC-1 gating.…”
Section: Discussioncontrasting
confidence: 56%
“…Intracellular metabolites such as ATP and NAD þ affect ClC-1 function by shifting the voltage dependence of common gating to more positive potentials and simultaneously reducing the minimum value of common gating curves [45][46][47][48][49][50] . These molecules bind to tandem CBS domains, which form the predominant structural feature of the extensive ClC-1 intracellular carboxy terminus.…”
Section: Resultsmentioning
confidence: 99%
“…ClC-1 channel activity was assessed using the same methods as detailed elsewhere [45][46][47] . Briefly, channel open probability (P o channel ) and open probability of the common gate (P o common ) were determined from tail-current amplitudes, measured at À 100 mV, following a 300-ms test pulse.…”
Section: Methodsmentioning
confidence: 99%
“…External pH was held at 7.5 while the internal pH was varied (5.5, black circles; 6.5, red triangles; 7.5, green squares; 8.5, yellow diamonds). (a,d ) The combined open probability, (b,d ) the slow-gate open probability and (c,e) the fast-gate open probability were determined as described by Bennetts et al 2007. The pipette and bath solutions were composed of (concentrations in mM) 110 NMDG, 110 HCl, 5 MgCl 2 , 1 EGTA, 10 HEPES, pH 7.50, adjusted by NaOH.…”
Section: Proton Dependence Of Fast Gatingmentioning
confidence: 99%